Conformational changes in Chikungunya virus E2 protein upon heparan sulfate receptor binding explain mechanism of E2–E1 dissociation during viral entry. Issue 6 (28th June 2019) - Sahoo, Bibekananda; Chowdary, Tirumala Kumar
Abstract : Receptor binding is the first step in viral cell entry. In enveloped virus cell entry, viral and host membrane fusion follows receptor binding. Viral surface receptor-binding protein associates with membrane fusion protein and masks its structure, to prevent pre-mature fusion activity. Dissociation of receptor-binding protein from fusion protein is an essential step before membrane fusion. Mechanism of receptor binding leading to dissociation of receptor binding and fusion protein is poorly understood in alphaviruses. Chikungunya virus (CHIKV), an alphavirus, re-emerged as a global pathogen in recent past. CHIKV surface envelope proteins, E2 and E1, function as receptor binding and fusion protein, respectively. Site of heparan sulfate (HS) receptor binding on E2–E1 heterodimer and its effect on E2–E1 heterodimer conformation is not known. Using molecular docking, we mapped HS binding to a positively charged pocket on E2 that is structurally conserved in alphaviruses. Based on our results from docking and sequence analysis, we identified a novel HS-binding sequence motif in E2. Purified E2 binds to heparin and HS specifically through charge interactions. Binding affinity of E2 to HS is comparable with other known HS–protein interactions ( K d ∼ 1.8 μM). Mutation of charged residues in the predicted HS-binding motif of E2 to alanine resulted in reduction of HS binding. Molecular dynamics (MD) simulations on E2, after docking HS, predicted allosteric domain movements. Fluorescence spectroscopy, far-UV circular dichroism spectroscopy, fluorescence resonance energy transfer experiments on HS-bound E2 corroborate our findings from MD simulations. We propose a mechanism where receptor-binding results in allosteric domain movements in E2, explaining E2–E1 dissociation.